Feasibility of spectral pH measurement during the low‐pH virus inactivation step of continuous therapeutic antibody production. (13th March 2020) - Goby, Jeffrey D.; Furuya, Kenji; Zimmermann, Eike; Beller, Justin A.; Schmitt, John M.; Cortese, Margot; Breit, Jeffrey F.; Coffman, Jonathan L.
Abstract: Acidic virus inactivation is commonly used during production of biotherapeutic products to provide virus safety in case of undetected virus contamination. Accurate pH measurement is required to ensure the product pH reaches a virus‐inactivating level (typically 3.5–3.7), and a level post‐inactivation that is appropriate for later purification steps (typically 5.5–7.5). During batch low‐pH inactivation in discrete tanks, potentiometric glass probes are appropriate for measuring pH. During continuous inactivation for 2–3 weeks in an enclosed product stream, probe calibration drift and lag may lead to poor accuracy, and operational difficulties when compensating for drift. Monitoring the spectral response of compounds (indicators) in the product stream whose spectra are pH‐sensitive offers a possible alternative way to measure pH without these drawbacks. Such indicators can already exist in the stream (intrinsic) or can be added (extrinsic). Herein are reported studies evaluating the feasibility of both.Promising ultraviolet screening results with the two extrinsics studied, thiamine and ascorbic acid, led to the addition of both to product stream samples titrated to different potentiometric pH values in the 3.3–4.5 range (a representative range encountered during continuous inactivation), and attempts to model pH using sample ultraviolet spectra. One model, based on variability in six spectral attributes, was able to predict pH of an independent sample set within ±0.07 units at the 95% confidence level. Since a typical inactivating pH tolerance is ±0.1 units, the results show that extrinsic indicators potentially can measure inactivation pH with sufficient accuracy. Suggested future steps and an alternative approach are presented.